MIR7–3HG, a MYC-dependent modulator of cell proliferation, inhibits autophagy by a regulatory loop involving AMBRA1. Issue 3 (4th March 2017) - Capizzi, Mariacristina; Strappazzon, Flavie; Cianfanelli, Valentina; Papaleo, Elena; Cecconi, Francesco
ABSTRACT: Macroautophagy/autophagy is a tightly regulated intracellular catabolic pathway involving the lysosomal degradation of cytoplasmic organelles and proteins to be recycled into metabolic precursors. AMBRA1 (autophagy and Beclin 1 regulator 1) has a central role in the autophagy signaling network; it acts upstream of MTORC1-dependent autophagy by stabilizing the kinase ULK1 (unc-51 like autophagy activating kinase 1) and by favoring autophagosome core complex formation. AMBRA1 also regulates the cell cycle by modulating the activity of the phosphatase PPP2/PP2A (protein phosphatase 2) and degradation of MYC. Of note, post-transcriptional regulation mediated by noncoding microRNAs (MIRNAs) contributes significantly to control autophagy. Here we describe a new role for the microRNA MIR7–3HG/MIR-7 as a potent autophagy inhibitor. Indeed, MIR7–3HG targets the 3′ untranslated region (UTR) of AMBRA1 mRNA, inducing a decrease of both AMBRA1 mRNA and protein levels, and thus causing a block in autophagy. Furthermore, MIR7–3HG, through AMBRA1 downregulation, prevents MYC dephosphorylation, establishing a positive feedback for its own transcription. These data suggest a new and interesting role of MIR7–3HG as an anti-autophagic MIRNA that may affect oncogenesis through the regulation of the tumor suppressor AMBRA1.